Observatories in space. - World Book, Inc. (Chicago, IL : World Book, 2010)
"An introduction to observatories in space with information about their history and use. Includes diagrams, fun facts, glossary, resource list, and index"--Provided by publisher.
Includes bibliographical references (p. 62) and index.
Keywords: Astronomical instruments -- Juvenile literature; Astronomical observatories -- Juvenile literature